Let x = first number and y = second number.
The first statement is expressed as
x*y = 713
The second statement is expressed as
x = y + 9
To find x, use the second equation in terms of y, that is y = x - 9. Then substituting it to the first equation yields
x*(x - 9) = 713
Answer:
(-2,1)
Step-by-step explanation:
AnswerAnswer:
Binomial
Step-by-step explanation:
there are 2 terms
Have a great day!
If it helped mark me as brainliest!
The answer is
G = [m1(veca1a2) + m2 (veca3a4) + m3veca5a6)] / (m1 + m2 + m3)
G= m1x5 + m2 x 4sqrt (2) + m3x 3sqrt (2) / 16 = 35 +4 x 3.7x sqrt (2) + 5.3 x3 4sqrt (2) / 16 =35 + 36<span> sqrt (2) / 16
G = 53.09
LOOK AT THE IMAGE
</span>
To find the simpliest form of a fraction, all you need to do is divide the numerator and denominator by their greatest common factor, in which in this case, is 2. And so all you need to do is divide the numerator(42) and the denominator(50) by 2, to get 21/25. This means that the simpliest form of 42/50 is 21/25.